Protective Effect of Omega-7 against Doxorubicin-Induced Cardiotoxicity in Male Rats - Mohammed H. Fadhel; Ali F Hassan (College of Pharmacy University of Baghdad, 2023)
Background: Doxorubicin is considered one of the most effective anticancer drugs, yet it is use is limited by its side effect mediated by the generation of reactive oxygen species. Omega-7, an antioxidant has shown to have a cardioprotective effect. Aim of the study: evaluate a possible protective effect of omega-7 against doxorubicin-induced cardiotoxicity in male rats. Methods: twenty-eight male rats were divided into 4 groups (7 for each group).  Group 1 (Negative control): healthy animals received normal saline orally as the vehicle for eight successive days and were sacrificed on day 9. Group 2 (positive control): animals that received a single dose of doxorubicin HCl (i.p 15mg/kg). Sacrificed the next day. Group 3: omega 7 was administered orally at a dose 100 mg/kg/day for eight days. On day 9, doxorubicin was administered IP (15mg/kg). Sacrificed on day 10. Group 4: omega 7 was administered orally at a dose 300 mg/kg/day for eight days. On day 9, doxorubicin was administered IP (15mg/kg) and sacrificed on day 10. Omega7 treatment started eight days before doxorubicin. The analysis was done on day 10.  Results: In the present study, catalase, and glutathione peroxidase were significantly increased in the omega7 treated group when compared to the negative control group (p<0.05) at the same time, malondialdehyde and reactive oxygen species were significantly decreased in the omega7 treated group when compared to the negative control group (p<0.05). Conclusion: this in vivo enzymatic study provides a piece of evidence for the possible effect of omega7 in the attenuation of cardiac toxicity in doxorubicin-treated patients